A Review on Fruit Juice Probiotication: Pomegranate - M. Mustafa, Siti; S. Chua, Lee; A. El- Enshasy, Hesham; A. A. Majid, Fadzilah; A. Malek, Roslinda (Current Nutrition & Food Science, 2016)
Foods and beverages containing live microbes (probiotics) are increasingly promoted by health professionals nowadays. The probiotic products in the market are mostly milk-based products, for instance yoghurts. There has been a high demand for the non-dairy probiotic products from those having the lactose intolerance problem and/or worry about the high cholesterol content. Therefore, fruit is now becoming the preferable matrix for probiotic delivery in human body. Fruits could be another promising carrier for probiotic strains, particularly from the genera of Lactobacilli and Bifidobacteria. Somehow, the cell viability and stability are highly fruit and strain dependent, in addition to the processing factors and storage temperature. In the present review, fruits, particularly pomegranate is critically highlighted as a potential fruity vehicle for probiotic microbiota. Pomegranate contains bioactive secondary metabolites (anthocyanins, ellagic acid derivatives and hydrolyzable tannins) and non-digestible carbohydrates (prebiotics). The low pH value of pomegranate juice could be compromised by mixing with other fruits or by protecting probiotics from acidic environment by microencapsulation. This review covers the previous works which were carried out on the fruit-based probiotic foods and beverages, supported by the mechanistic explanation on the action of probiotics in human body.
Keywords: Probiotic foods